Current ratio, return on assets and company size to capital structure in manufacturing companies in the food and beverage subsector - Oktaviani, Niken Ayu; Nurhayati, Nurhayati; Safitri, Rifani Diah; Haryadi, Didit; Wahyudi, Wahyudi (International Journal of Applied Finance and Business Studies, 2024)
This study investigates the interaction between the current ratio, return on assets, company size and capital structure in Indonesia's food and beverage sector. The goal is to gain insight into how these factors interact and affect the overall value of a company in a particular region and industry. This analysis uses quantitative methods based on financial data and relevant metrics for a sample of 15 food and beverage sector companies operating in Indonesia. This study examines the relationship between the current ratio, return on assets, and company size to capital structure through statistical analysis and linear regression modelling techniques with SPSS version 26. The results showed that the current ratio did not significantly affect the capital structure. Return on assets does not have a significant effect on the capital structure. Then, the size of the company has a significant influence on the capital structure. The current ratio, return on set, and company size affect the capital structure simultaneously. The findings contribute to the existing literature on company valuations by providing empirical evidence specific to the food and beverage sector. The research has implications for policymakers, investors, and managers, as it offers valuable insights into the factors driving shaping capital structures in the industry, helping stakeholders make decisions and strategies to improve performance and competitiveness. Provide benefits in the context of financial management